(untitled) (El Taco en la Brea, 2019)
This article examines questions derived from the «ethics» of «responsibility» founded by Jacques Derrida. We focus on the text Who comes after the subjetct?, edited by Eduardo Cadava, Peter Connor y Jean-Luc Nancy in 1991, and on the work of two of his «heiresses»: Avital Ronell y Anne Dufourmantelle. We ask how these works reinvigorate the discussion of the politics and the ethics in the present.